Thomas Reid on the Improvement of Knowledge. Issue 2 (June 2019) - Shrock, Christopher A.
Abstract : Thomas Reid often seems distant from other Scottish Enlightenment figures. While Hume, Hutcheson, Kames, and Smith wrestled with the nature of social progress, Reid was busy with natural philosophy and epistemology, stubbornly loyal to traditional religion and ethics, and out of touch with the heart of his own intellectual world. Or was he? I contend that Reid not only engaged the Scottish Enlightenment's concern for improvement, but, as a leading interpreter of Isaac Newton and Francis Bacon, he also developed a scheme to explain the progress of human knowledge. Pulling thoughts from across Reid's corpus, I identify four key features that Reid uses to distinguish mature sciences from prescientific arts and inquiries. Then, I compare and contrast this scheme with that of Thomas Kuhn in order to highlight the plausibility and originality of Reid's work.